Unveiling The Impact Of Economic And Political Globalisation On The Efficiency Of Microfinance Institutions - Fakarudin Kamarudin; Mohamad Khair Afham Muhamad Senan; Hafezali Iqbal Hussain; Janusz Michałek; Nazratul Aina Mohamad Anwar (Centre of Sociological Research, 2024)
Microfinance Institutions (MFIs) strive to alleviate poverty by offering financial access and services to the poor in society. MFIs play a significant role in a country's social and economic advancement. This study aims to examine the relationship of the economic and political globalisation with the social and financial efficiency of MFIs in the Philippines and Malaysia from 2012 to 2020. There are two types of analysis adopted in this study: the non-parametric Data Envelopment Analysis (DEA) and the multiple panel regression model. In the first stage, the DEA approach is employed to determine the MFIs’ level of efficiency. Next, the determinants of financial efficiency and social efficiency are identified through panel regression. The results of the robustness test show that MFIs have better and more effective financial efficiency compared to social efficiency. Therefore, this result shows that the MFIs concentrate more on profitability and sustainability of the operations and they tend to neglect their primary goal in terms of the social function, i.e., reducing poverty, since the scores for financial efficiency are higher than those for social efficiency. Furthermore, the MFIs, government, policymakers, investors, and future researchers benefit from the outcomes of this study, as they can obtain a comprehensive insight on the efficiency of MFIs and the variables that could contribute to the efficiency in MFIs.